2014
DOI: 10.1016/j.ajpath.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatocytes and Hematolymphoid Dual Reconstitution in Treosulfan-Conditioned uPA-NOG Mice

Abstract: Human-specific HIV-1 and hepatitis co-infections significantly affect patient management and call for new therapeutic options. Small xenotransplantation models with human hepatocytes and hematolymphoid tissue should facilitate antiviral/antiretroviral drug trials. However, experience with mouse strains tested for dual reconstitution is limited, with technical difficulties such as risky manipulations with newborns and high mortality rates due to metabolic abnormalities. The best animal strains for hepatocyte tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…This has recently been reported by transplanting adult human hepatocytes and mismatched HSC derived from fetal human liver tissue, which resulted in doubly engrafted animals [7,8]. However, to avoid allogeneic immune responses both grafts should be derived from the same human donor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has recently been reported by transplanting adult human hepatocytes and mismatched HSC derived from fetal human liver tissue, which resulted in doubly engrafted animals [7,8]. However, to avoid allogeneic immune responses both grafts should be derived from the same human donor.…”
Section: Introductionmentioning
confidence: 99%
“…Human HSC can also be obtained from adults [9] but hepatocytes from these same individuals are rarely available. When fetal hepatoblasts are combined with syngeneic HSC the liver graft either was lost [7] or the engrafted hepatoblasts fail to expand to high levels [10,11]. Together, these findings suggest that allogeneic doubly reconstituted mice can be generated but that human fetal hepatoblasts insufficiently engraft human liver chimeric mice, which limits the generation of syngeneic doubly reconstituted mice.…”
Section: Introductionmentioning
confidence: 99%
“…Engraftment efficiency appears to be strain-dependent as some studies report more robust engraftment with these fetal progenitor cells in AFC8 mice [25]. However, similar to liver transplantation in humans, close donor matching may not be imperative as it was recently shown that extensive humanization of both the liver and the immune system can been achieved through the use of allogeneic adult hepatocytes and HSCs without any overt rejection [34,35]. Dually engrafted mice mounted virus-specific immune responses following HBV infection, resulting in human-specific liver fibrosis [36].…”
Section: Host Adaptation: Xenotransplantation Modelsmentioning
confidence: 99%
“…However, studies on HCV immunopathogenesis, primary (human) adaptive immune response and vaccine efficacy in mice would require both a human liver graft and a functional (human) immune system in one and the same recipient animal. This has recently been achieved by combining adult human hepatocytes and human CD34 + hematopoietic stem cells (HSCs) from different human donors [110,111]. Although the authors did not show HCV infection, the high human engraftment levels suggest that these mice could become viremic upon HCV challenge.…”
Section: Animal Models To Study Hcv Infectionmentioning
confidence: 99%